The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.32604/cmc.2023.034655
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence-Enabled Chatbots in Mental Health: A Systematic Review

Abstract: Clinical applications of Artificial Intelligence (AI) for mental health care have experienced a meteoric rise in the past few years. AIenabled chatbot software and applications have been administering significant medical treatments that were previously only available from experienced and competent healthcare professionals. Such initiatives, which range from "virtual psychiatrists" to "social robots" in mental health, strive to improve nursing performance and cost management, as well as meeting the mental healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Although AI-enabled solutions demonstrate potential in the field of mental health, further research is required to examine the ethical and societal implications of these technologies. Furthermore, it is necessary to build effective research and medical practices within this innovative area [ 50 ]. Overall, findings suggested that acceptance does not only depend on the design of the chatbot software but also on the characteristics of the user, and most prominently on self-efficacy, state anxiety, learning styles, and neuroticism personality traits.…”
Section: Discussionmentioning
confidence: 99%
“…Although AI-enabled solutions demonstrate potential in the field of mental health, further research is required to examine the ethical and societal implications of these technologies. Furthermore, it is necessary to build effective research and medical practices within this innovative area [ 50 ]. Overall, findings suggested that acceptance does not only depend on the design of the chatbot software but also on the characteristics of the user, and most prominently on self-efficacy, state anxiety, learning styles, and neuroticism personality traits.…”
Section: Discussionmentioning
confidence: 99%
“…AI tools offer the ease of accessing medical information and advice, encouraging individuals to gather initial information regarding their symptoms and possible conditions (Lee & Yoon, 2021). This accessibility facilitates the initial collection of information regarding symptoms and potential conditions (Madhu et al., 2017), circumventing the immediate need for medical consultation (Ahuja, 2019; Omarov et al., 2023). AI‐powered tools provide immediate information (Kumar et al., 2022), allowing individuals to input their symptoms and receive prompt suggestions regarding potential diagnoses or underlying causes (Baker et al., 2020).…”
Section: Understanding Self‐diagnosing Mental Healthmentioning
confidence: 99%
“…While not a substitute for professional diagnosis, these tools can complement professional care by guiding individuals towards help, assisting practitioners in monitoring progress, and contributing valuable research data. AI-powered assessments and chatbots play a role in modern mental healthcare, but their integration should always be part of a comprehensive approach that includes professional evaluation and treatment (Abd-alrazaq et al, 2022(Abd-alrazaq et al, , 2023Omarov et al, 2023;Rathnayaka et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of AI and wearable devices allows for continuous, objective patient monitoring, offering insights into mood changes and treatment effects, thereby enhancing mental health care and research (Nahavandi et al, 2022 ). Integrating AI algorithms with real-time data from wearables and sensors marks a substantial stride forward, enabling the creation of personalized and responsive mental health systems (Boucher et al, 2021 ; Omarov et al, 2023 ). Personal wearable devices like smartwatches and fitness trackers offer real-time data collection for healthcare.…”
Section: Introductionmentioning
confidence: 99%